The presence of STAT1-positive tumor-associated macrophages and their relation to outcome in patients with follicular lymphoma - T Alvaro; M Lejeune; FI Camacho; MT Salvado; L Sanchez; JF Garcia; C Lopez; J Jaen; R Bosch; LE Pons; C Bellas; MA Piris (Haematologica, 2006)
BACKGROUND AND OBJECTIVES: The presence of tumor-associated macrophages (TAM) is a prognostic factor for survival in follicular lymphoma (FL). Overexpression and/or activation of the signal transducer and activator of transcription 1 (STAT1) in these TAM have also been observed. The aim of this study was to determine the extent to which macrophages are present in FL and to investigate the expression of STAT1 in these cells. DESIGN AND METHODS: We retrospectively analyzed 211 patients with distinct stages and grades of FL. Expression of the CD68 proteins, chosen as a marker for macrophages, and STAT1 was quantified by immunohistochemistry and double immunofluorescence. RESULTS: Automated determinations revealed the presence of CD68-positive macrophages in all FL tissues studied (mean 57.6+/-45.1 cells/field), while STAT1 protein was expressed in 29.94% of cases. Double-fluorescence staining confirmed that STAT1 protein co-localized exclusively with CD68, indicating the presence of a subset of STAT1-expressing TAM localized principally in the vicinity of tumor cells. Multivariate analysis showed that, besides the Follicular Lymphoma International Prognostic Index (FLIPI) classification, expression of STAT1 was an important independent prognostic factor for shorter overall survival in FL. INTERPRETATION AND CONCLUSIONS: These results demonstrate the presence of STAT1-expressing TAM in FL and their association with an adverse outcome, thus emphasizing the relevance of non-tumor cells in the control of the growth and survival of lymphoma cells.